The fans’ carnival in Bogotá: a social study on the celebration in football - Castro Lozano, John Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Since the 1990s, the general eastern tribune and then the north side and the south side of the Nemesio Camacho “El Campín” stadium showed the emergence of a generation of fans who transformed the boredom, monotony and passivity of fans, as they eventually expressed their emotions during football games. In 1993 Blue Rain was organized and in 1996 it was transformed into Comandos Azules #13, organized groups of fans of the Los Millonarios Sports Club in Bogotá, usually called “bravas bravas”, who - through applause, songs, jumps, musical instruments, billboards, gunpowder and columns of smoke, among others—exalt their football identity, encourage their club and, in addition, maximize their rivalries. The purpose of the article is to interpret the festive expressions—manifested by the fans gathered in the brave bars of Bogotá—around the football games in “El Campín.” In this aspect, the article is organized into eight sections: “Introduction”, “The methodological aspects”, “Barra del Búfalo”, “And here we come”, “Inspiration came from the south”, “The brave arrived”, “I swear I will encourage you” and “Conclusions”. Finally, the methodology was oriented through observation, participation and interviews, specific techniques of ethnographic fieldwork. The social actors are fans of Millonarios Football Club in Bogotá grouped in “Blue Rain” and “Comandos Azules”.